Oleuropein Prevents OVA‐Induced Food Allergy in Mice by Enhancing the Intestinal Epithelial Barrier and Remodeling the Intestinal Flora. Issue 24 (11th November 2022) - Guo, Yuanjie; Ma, Yu; Ma, Liyuan; Guo, Zixin; Xiao, Yingliang; Liu, Yunjun; Li, Jie; Wang, Shengnan; Liu, Yixiang
Abstract : Scope: This study assesses whether oleuropein prevents ovalbumin (OVA)‐induced food allergy (FA) and investigates the underlying mechanisms. Methods and results: A Balb/c FA mouse model is established and maintained for 7 weeks. The subjects are administered OVA by oral gavage to induce FA and supplemented with different oleuropein doses (1.00–20.00 mg kg −1 per day) to evaluate its preventative efficacy. The results indicate that oleuropein effectively alleviates OVA‐induced allergy symptoms and promotes temperature elevation in sensitized mice. The secretion of serology‐specific OVA‐immunoglobulin (Ig)E, OVA‐IgG, and histamine is inhibited in the sensitized mice. Oleuropein dramatically upregulates the expression of intestinal tight junction (TJ) proteins, regenerating gene (Reg) IIIγ, and interleukin (IL)‐22, enhancing the physical and biochemical barrier function of the intestinal epithelium. Additionally, oleuropein improves the immune homeostasis of the intestinal epithelium by affecting the function of mucosal mast cells and regulatory T (Treg) cells. The disordered intestinal flora of the sensitized mice also improves after oleuropein administration. Conclusions: These findings suggest that oleuropein prevents FA by enhancing intestinal epithelial barrier function and improving immune homeostasis and intestinal flora in sensitized mice. Therefore, diets rich in oleuropein should be recommended for people with FA. Abstract : Oleuropein is effective in preventing food allergy (FA). The results showed that oleuropein was effective in alleviating allergic symptoms in mice. The secretion of serology‐specific ovalbumin (OVA)‐immunoglobulin (Ig) E, OVA‐IgG and histamine was inhibited. Oleuropein enhanced the physical and biochemical barrier function of the mouse intestinal epithelium and improved the immune homeostasis and intestinal flora of the intestinal epithelium.